BEVERAGE PREPARATION FROM FISH HYDROLYSATES. - PRABHU, P. V. PRABHU V; RADHAKRISHNAN, A G; JAMES, M ARUL (Fishery Technology, 2017)
A method for the preparation of energy food incorporating fish hydrolysates, sugar, cocoa, malt extract etc. is described. The product has good consumer appeat The preparation does not impart any bitter taste of the hydrolysate to the final product irrespective of the type of fish used for preparing the hydrolysate. It freely mixes with hot or cold milk and the resulting drink is adjudged to be very palatable.